Nurse practitioners in medical rehabilitation settings: A description of practice roles and patterns. Issue 4 (27th June 2013) - Kosevich, Gwen; Leinfelder, Anna; Sandin, Karl J.; Swift, Erin; Taber, Susan; Weber, Rebecca; Finkelstein, Marsha
Abstract Purpose To describe nurse practitioner (NP) roles in medical rehabilitation settings. Data source Description of practice by rehabilitation NPs and physicians. Conclusions NPs increasingly function in medical rehabilitation settings as independent or collaborative care providers. This article describes their roles at a large rehabilitation institute in acute care consultation/liaison, acute rehabilitation, and ambulatory settings. The organization has experienced greater physician efficiency and practice scope, without erosion of subjective or objective quality measures and outcomes. The authors provide specific examples of NP roles in intrathecal baclofen and cancer rehabilitation programs. Implications for practice Advanced practice nurses can provide efficacious care to people with disabilities, resulting in cost savings, improved outcomes, and high value. Patient care by NPs is beneficial for the physicians so that they may extend their clinical realm, spend more time doing research, and participate in medical leadership.